Quantum Leadership of Teacher in Improving the Quality of Education Based on Pesantren - Akmal Mundiri; Renita Wijhi Ningtias (Tarbiyah Departement collaboration with AMCA, 2019)
Leadership as a complex process is a leaders introspecsion in improving todays education quality. In improving education quality in pesantren, an educator as a learning leader is prioritized to have special skills in managing learning. Quantum Leadership as a leadership concept that can influence students in teaching learning process, so it can be conducive, effective and efficient. This research uses a case study located in Nurul Jadid Islamic Boarding School, Probolinggo Regency. The students prioritize all the dynamics of education. Educator quantum leadership can be a hologram in education, so it becomes guides for students. In addition, Quantum Leadership also have an important role in improving education quality in pesantren with some characteristics; seeing and dreaming, nurture with respect, nurture with love, nurture with care, visionary supervisition, creating point for society, empathy, empowerment, helping students develop and success, giving students top priority, having behavior ethically and persuasi communication.